Which One? Choosing Favorite Robot After Different Styles of Storytelling and Robots’ Conversation - Velentza, Anna-Maria; Fachantidis, Nikolaos; Pliasa, Sofia (Frontiers in Robotics and AI, 2021)
The influence of Human-Care Service Robots in human-robot interaction is becoming of great importance, because of the roles that the robots are taking in today and future society. Thus, we need to identify how humans can interact, collaborate, and learn from social robots more efficiently. Additionally, it is important to determine the robots’ modalities that can increase the humans’ perceived likeness, knowledge acquisition and enhance human-robot collaboration. The present study aims to identify the optimal social service robots’ modalities that enhance the human learning process, level of enjoyment from the interaction, and even attract the humans’ attention to choose a robot to collaborate with it. Our target group was college students, pre-service teachers. For this purpose, we designed two experiments, each one split in two parts. In both the experiments human participants had the chance to watch the Nao robot, performing a storytelling about the history of robots in a museum- educational activity via video annotations. The robot’s modalities were manipulated on its body movements (expressive arm and head gestures) while performing the storytelling, friendly attitude expressions and storytelling and personality traits. After the robot’s storytelling, participants filled out a knowledge acquisition and a self-reported enjoyment level questionnaire. In the second part, we introduce the idea of participants witnessing a conversation between the robots with the different modalities and were asked to choose the robot with which they want to collaborate in a similar activity. Results indicated that participants prefer to collaborate with cheerful personality robots with expressive body movements. Especially when they were asked to choose between two cheerful, expressive body movements robots, they preferred the one which originally gave them the storytelling. Moreover, participants did not prefer to collaborate with an extremely friendly attitude storytelling style robot.